Job satisfaction among nurses in Iran: does gender matter? - Morteza Akbari; Afsaneh Bagheri; Aliakbari Fathollahi; Majid Darvish (2020)
Job satisfaction has attracted increasing attention of scholars of different disciplines in recent years. However, there are limited studies on nurses' job satisfaction and the impact of gender on nurses' satisfaction with their job, particularly in Iran as a developing economy. The paper aimed to examine job satisfaction among Iranian nurses. Specifically, this study aimed to explore how Iranian male and female nurses are different in their overall and the dimensions of their job satisfaction.The population for this study was nurses who worked in public and private hospitals in Tehran, the capital city of Iran. A sample of 146 nurses in eight different hospitals was selected to participate in this survey using the random sampling method. The sample consisted of 81 female and 65 male nurses.Our findings revealed that job satisfaction of both male and female nurses was at a median level. Furthermore, the level of overall job satisfaction among female was low, and the mean score of the dimensions of their job satisfaction was lower than their male counterparts. Furthermore, according to the independent t-test analysis, the difference between all dimensions of job satisfaction of females and males was significant, except for their satisfaction with the specific job of nursing.The findings of this study suggested that overall female nurses' nursing job satisfaction was lower than males in all dimensions except for their satisfaction with their job. Yet, there was no significant difference between female and male nurses in all of the dimensions of their job satisfaction except for their satisfaction with their specific nursing job. This finding forms a basis for the development of management principles and practices, specifically in relation to human resource management in public and private hospitals in Iran.